Prevalence and factors associated with breastfeeding in a population with good literacy - Rajasekar, Geetha (International Journal Of Community Medicine And Public Health, 2017)
Background: Recent studies in the scientific world show that countries with high income levels and high maternal education have poorer breast feeding rates. This study was done in a population with good literacy with an objective to assess the knowledge, beliefs, practices, prevalence of breast feeding and factors associated with it among women with children less than two years of age. Methods: This was a cross sectional study done among 183 women at a tertiary hospital of south India in a population with female literacy 77% and male literacy 90%. Knowledge, beliefs and practices were assessed by validated questionnaire. Data entry and analysis were done with Epidata 3.1 and SPSS18 software. Results: The prevalence of early initiation of breast milk was 56.3% (95% CI: 48.98 to 63.62), colostrum to newborn 84.2 % (95% CI: 78.82 to 89.58),exclusive breast feeding (EBF)10.6% (95% CI: 6.02 to 15.18), predominant breast feeding 80.6% (95% CI: 74.72 to 86.48) and delayed complimentary feeding was 8.8% (95% CI: 4.58 to 13.02).Only 51% (95% CI: 42.92 to 57.68) had health professional guidance and among them only 29.34% (95% CI: 19.84 to 38.83) had received it after delivery. Lower segment caesarean section (LSCS) had 3.9 times (95% CI: 1.95 to 8.05) risk of late initiation of breast milk. Breast feeding information from relatives had protective effect from late initiation of breast milk with odds ratio 0.33 (95% CI: 0.16 to 0.66). Women who had not received health professional guidance had 3.5 times (95%CI: 1.13 to 11.00) risk of not practicing exclusive breast feeding. Conclusions: The knowledge and beliefs about breast feeding were encouraging. Inspite of good literacy women need guidance from health personnel for EBF. Mothers who had delivered by LSCS have to be given help to initiate breast feeding earlier.